2000
DOI: 10.1021/ja0021058
|View full text |Cite
|
Sign up to set email alerts
|

Pentavalent Organo-Vanadates as Transition State Analogues for Phosphoryl Transfer Reactions

Abstract: Pentavalent organo-vanadates have been put forth as transition state analogues for a variety of phosphoryl transfer reactions. In particular, uridine 2′,3′-cyclic vanadate (U>v) has been proposed to resemble the transition state during catalysis by ribonuclease A (RNase A). Here, this hypothesis is tested. Lys41 of RNase A is known to donate a hydrogen bond to a nonbridging phosphoryl oxygen in the transition state during catalysis. Site-directed mutagenesis and semisynthesis were used to create enzymes with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 52 publications
5
42
0
Order By: Relevance
“…52,72 Lys41 Several substitutions at residue 41 inactivate RNase A. Lys41 has been shown previously to be critical for ribonucleolytic activity, as it donates a hydrogen bond to the pentavalent transition state. 51,73 K41A RNase A has a k cat /K M value that is 10 4 -fold lower than that of the wild-type enzyme. 74 Yet, Lys41 can be replaced by arginine with only a 10 2 -fold decrease in catalytic activity.…”
Section: His12 and His119mentioning
confidence: 91%
“…52,72 Lys41 Several substitutions at residue 41 inactivate RNase A. Lys41 has been shown previously to be critical for ribonucleolytic activity, as it donates a hydrogen bond to the pentavalent transition state. 51,73 K41A RNase A has a k cat /K M value that is 10 4 -fold lower than that of the wild-type enzyme. 74 Yet, Lys41 can be replaced by arginine with only a 10 2 -fold decrease in catalytic activity.…”
Section: His12 and His119mentioning
confidence: 91%
“…49 Recently, the potency of the vanadate-nucleoside complex was investigated with several mutants of ribonuclease and these investigators confirmed the conclusion that the vanadiumnucleoside is not a "true and perfect" transition analogue. 50 Although small structural differences existing in the mutants were not considered, which could diminish the observed potency of the vanadate-nucleoside complex as an inhibitor, the fact that vanadate-nucleosides are likely to be potent, but not perfect, transition state analogues is likely to be confirmed. Indeed, considerations regarding what types of phosphorylase reactions V-complexes may be most effective against have been extensively considered.…”
Section: Vanadium-nucleoside Complexes: Functional Inhibitors Of Ribomentioning
confidence: 99%
“…Specifically, these amino acids interacted with vanadate in a manner that was incongruous with mechanistic evidence supporting a concerted, imidazole-mediated acid/base mechanism in which Lys41 ameliorates negative charge buildup on the nonbridging oxygens. Later studies offered explanations citing the apparent plasticity of the ''oxyvanadate framework'' (Ladner et al 1997) and fundamental differences in the vanadate electronics compared with phosphate (Messmore and Raines 2000). The salient and admonitory conclusion is that the bound vanadate was stabilized by the active site of RNase A, but through interactions irrelevant to a widely accepted view of the transition state.…”
Section: Caveats For the Use Of Vanadatementioning
confidence: 99%